Relationship between lower limb asymmetry and judo-specific test performance - Kons, R. L.; Diefenthaeler, F.; Orssatto, L. B. R.; Sakugawa, R. L.; da Silva Junior, J. N.; Detanico, D. (Sport Sciences for Health, 2020)
Purpose: This study aimed to verify the relationship between bilateral lower limb asymmetry and performance in the Special Judo Fitness Test (SJFT). Methods: Twelve male judo athletes (23.0 ± 3.9 years) participated in this study. Athletes first performed ultrasonography assessments and unilateral countermovement jumps (CMJ), and 48 h after they performed the SJFT. A t test was used to compare stronger and weaker limbs and Pearson`s correlation was used between asymmetry level and SJFT performance (a = 5%). Results: Our data showed higher values for stronger limb than weaker limb for echo intensity (EI) and muscle thickness (MT) in the rectus femoris and vastus lateralis. Negative correlation was observed between jump height asymmetry and SJFT number of throws (r = - 0.68, p = 0.014), peak velocity asymmetry and third series of SJFT (SJFT30B) (r = - 0.58, p = 0.045), while large positive correlation was observed for maximal force and jump height asymmetry with SJFT index (r = 0.50, p = 0.044; and r = 0.58, p = 0.038, respectively). For ultrasound variables, negative correlation was observed between EI in the vastus lateralis asymmetry and SJFT30B (r = - 0.59, p = 0.041). Conclusion: We conclude that bilateral lower limb asymmetry in unilateral CMJ and EI of vastus lateralis have negative influence in SJFT performance.